Nanotopographic carbon nanotube thin-film substrate freezes lateral motion of secretory vesicles - Zhang, Jing (2012)
Thin-film carbon-nanotube networks can interface with living neuroendocrine PC12 cells and support their growth and proliferation. Interestingly, as revealed by total-internal-reflection fluorescence microscopy, the nanoroughness created by the carbon-nanotube net physically deforms the 5 nm thick cell membrane with high local curvature, and significantly impedes the lateral motion of subplasmalemmal secretory vesicles.